On the Issue of Risk Assessment of Investment Projects Using Fuzzy Sets - M. SINYTSKYI (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Approaches to risk assessment of investment projects with the use of economic criteria in the form of fuzzy values have been briefly analyzed.  Cases where the project criterion is represented by a fuzzy number with a membership function that has a shape of a trapezoid, a Gauss curve and a bell (flat top and asymmetric “wings”) have been considered.The calculation formulae for assessing the risks of investment projects, suitable to be used in financial management practices and decision support systems, are obtained using analytical-numerical methods in «MatLab®», «Statistica®» and “Mathematics®» (Wolfram) applications.